Gestão comparativa de sistemas de coleta e tratamento de esgoto visando a universalização e a sustentabilidade - Tochetto, Márcio (2021)
Basic sanitation has been present throughout the evolution of the human species. For several periods there was disregard for this service, and as a consequence, it was always followed by major epidemics, the appearance of new contagious diseases and high population mortality rates. Thus, a direct relationship between the quality of sanitation and the emergence of epidemics has been evidenced. The years, decades and centuries have passed and the sector still has low rates of provision of this service and few prospects of service in the short and medium term are glimpsed in Brazil. In this scenario, this research aims to discuss and compare alternatives between the types of sewage collection, transportation and treatment systems, collective or individual, that can provide economic viability and reach the expectations of government officials, administrators and society in general regarding the service desired coverage levels. The methodological procedures were divided into characterization of the types of systems, whether collective systems: absolute, unitary or mixed separator; or individual systems; identification of ways of managing sewage collection and treatment systems, simple or composite systems; discussion of regulation and applied legislation and the acceptability of the population as to the counterpart to which it will be submitted. The research is linked to current and contemporary literature, data from companies that provide basic sanitation services - sanitary sewage -, national and international, journals, scientific articles and other sources relevant to the work. The social, economic and environmental aspects are inserted in the study as an essential part in the basis of the proposed alternatives, its balance being the ideal point to be considered. Study of best practices, drawing up management flows that comprise the stages of planning, implementation, execution, operation and maintenance are part of the scope of the research. In this area, the diagnosis of the sector in Brazil was detailed, presenting the distinctions regarding the level of investment and the quality in the management system and its reflection in the service levels, as well as the quality and impacts on society, the economy and the environment. Percapta or per-household values provide input to stakeholders for decision making regarding the choice of which system to apply. A general synthesis can be obtained with a view to geographic, population or local cultural aspects with interference in the analysis and proposition with clear financial perspectives in relation to the objective to be served.